UVH6 regulates osmotic and heat stress tolerance by modulating transcription - Kobayashi, Koya; Murakoshi, Yusuke; Kanamori, Kazuki; Hidema, Jun; Masuda, Goro; Tanaka, Keisuke; Yotsui, Izumi; Sakata, Yoichi; Taji, Teruaki (Frontiers in Plant Science, 2025)
Nucleotide excision repair (NER) is a critical mechanism for repairing DNA damage, including UV-induced lesions and chemically induced adducts. The UVH6 gene encodes a subunit of the transcription factor IIH complex and is essential for both NER and transcription initiation. In Arabidopsis thaliana, UVH6 mutations impair DNA repair, enhance UV sensitivity, and decrease heat stress tolerance. We here isolated acquired osmotolerance–defective12 (aod12) mutant derived from osmotolerant Bu-5 accession; this mutant had pale green leaves and was osmosensitive and heat sensitive. Genetic and molecular analyses revealed that a mutation in UVH6 underlies these phenotypes of aod12. RNA sequencing demonstrated that UVH6 is necessary for appropriate transcriptional responses under osmotic stress, as expression of some stress-response genes was altered in aod12. Expression of pathogenesis-related genes and cell death were increased, indicating that immune responses detrimental to osmotolerance were activated. Interestingly, UVH6-mediated osmotolerance was independent of its canonical DNA repair function, as other NER-related mutants (xpf, xpg, ercc1) were not osmosensitive. Signaling pathways involving UVR8 and SOG1 were not implicated in UVH6 mutation–induced immune responses, suggesting a novel regulatory mechanism linking transcriptional control and stress tolerance. This study highlights UVH6 as a key integrator of genome stability, transcription, and stress resilience in plants.